Pengaruh Keputusan Investasi Dan Keputusan Deviden Terhadap External Financing Needs Dengan Variabel Moderating Profitability Pada Perusahaan Manufaktur Yang Go Public di Bursa Efek Jakarta - Wathan, Farsyan (Program Doktor Ilmu Ekonomi, 2008)
Manufacturing industry in doing the business operation is determined by the factors, i.e. investment work, dividend work, profitability, and external financing, so it can be known the operational work from the companies. Problem formulas in this research are: (1) whatever the investment decisions and dividend decisions influence significantly towards profitability, (2) whatever the investment decisions and dividend decisions influence significantly towards External Financing Needs and (3) whatever the profitability influences significantly towards External Financing Needs. This research design uses descriptive methods which will observe the company external fund needs, if it happens the value variations in investment decisions and dividend decisions with the profitability moderating variables in an empiric-linear relationship pattern. The research object is the company in manufacturing industry fields for the periods of 2002-2004 by the data in financing report forms from the prepared company by Jakarta Stock Exchange (Bursa Efek Jakarta). The used variables consist of 3, i.e. bound variables (Y) which contain Debt to Total Assets (Y1) and Debt To Equity (Y2), free variables (X) which contain Investment Decisions (X1) and Dividend Policy (X2), and also moderating variables (Z) are Profitability that consists of Margin Profit Net indicator (on Sales) (Z1), Return on Equity (Z2), and Return on Investment (Z3). The empirical test which is used in this research isPartial Least Square (PLS). The data results empirically show that: (1) investment decision variables and dividend decisions do not influence significantly towards profitability in go- public company in Jakarta Stock Exchange (Bursa Efek Jakarta), with t-calculation is smaller than t table = 1.99. (2) investment decision variables influence significantly towards External Financing with the value of t-calculation is 8.460 is bigger than t table = 1.99. (3) dividend decisions do not influence significantly towards External Financing in go-public company in Jakarta Stock Exchange (Bursa Efek Jakarta), and (4) profitability variables influence significantly towards External Financing in go-public company in Jakarta Stock Exchange (Bursa Efek Jakarta), with the value of t statistic of profitability direction towards External Fianancing in the value of 3.058 > t table = 1.99. Keywords: investment decisions, dividend decisions, profitability, external financing needs.